2019
DOI: 10.1007/s00334-019-00715-8
|View full text |Cite
|
Sign up to set email alerts
|

Four centuries of vegetation change in the mid-elevation Andean forests of Ecuador

Abstract: Mid-elevation Andean ecosystems have immense species richness and endemism. Taxonomic composition is known to change through time on the eastern slopes of the Andes as a result of climatic change and disturbance events, both natural and by human actions. Fossil phytoliths can capture local scale vegetation changes, especially among monocotyledonous plants. Phytolith production is high in grasses and palms, plant groups that are particularly sensitive to climatic changes and disturbance events in Andean ecosyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The same structures seem to exist further north towards the "La Bonita" area in the headwaters of the Putumayu River. If all this evidence gets confirmed, then the area has to be incorporated within a new model of biocultural heritage of this ecological legacy, indicating that the cloud forest is actual a "feral" community that has settled again, with the ecological legacy of about four centuries of abandonment [28,42,49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same structures seem to exist further north towards the "La Bonita" area in the headwaters of the Putumayu River. If all this evidence gets confirmed, then the area has to be incorporated within a new model of biocultural heritage of this ecological legacy, indicating that the cloud forest is actual a "feral" community that has settled again, with the ecological legacy of about four centuries of abandonment [28,42,49].…”
Section: Discussionmentioning
confidence: 99%
“…A discursive analysis of population dynamics in this wide region showed that, despite the number of inhabitants (ca. 16,500-24,500) by the year 1577 [72] was from 2.4 to almost 3.6 times below the census figures for the year 2000, it is comparable to the present number of 17,268 people [28,58]. Therefore, it is important to observe current ethnographic data to understand the process of historical and ongoing cultural transformation.…”
Section: Pre-hispanic Settlements and Historicitymentioning
confidence: 99%
See 1 more Smart Citation
“…All soil surface samples (n = 42) were processed for phytoliths at the Palaeoecology Laboratory at the University of Amsterdam (UvA), using a subsample containing 1 cm 3 of soil. At the onset of laboratory processing, 56,000 microspheres (Microparticles GmbH, Lot: SiO2-R-L3519-3, ø 15.29 μm, SD 0.49 μm) were added to each sample to calculate phytolith concentrations (Huisman et al, 2019;Witteveen et al, 2022). A series of chemical treatments, with 33% hydrogen peroxide (H 2 O 2 ), 10% hydrochloric acid (HCl) and potassium manganate (KMnO 4 ), were performed on each sample.…”
Section: Laboratory Analysismentioning
confidence: 99%